Active capacitor voltage stabilisation in a medium-voltage flying-capacitor multilevel active filter - Hansmann, Chirstine Henriette (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2005.